Bone Engineering Scaffolds With Exosomes: A Promising Strategy for Bone Defects Repair - Zhang, Mingming; Li, Yi; Feng, Taojin; Li, Ran; Wang, Zhongqi; Zhang, Licheng; Yin, Pengbin; Tang, Peifu (Frontiers in Bioengineering and Biotechnology, 2022)
The treatment of bone defects is still an intractable clinical problem, despite the fact that numerous treatments are currently available. In recent decades, bone engineering scaffolds have become a promising tool to fill in the defect sites and remedy the deficiencies of bone grafts. By virtue of bone formation, vascular growth, and inflammation modulation, the combination of bone engineering scaffolds with cell-based and cell-free therapy is widely used in bone defect repair. As a key element of cell-free therapy, exosomes with bioactive molecules overcome the deficiencies of cell-based therapy and promote bone tissue regeneration via the potential of osteogenesis, angiogenesis, and inflammation modulation. Hence, this review aimed at overviewing the bone defect microenvironment and healing mechanism, summarizing current advances in bone engineering scaffolds and exosomes in bone defects to probe for future applications.